Soil sampling preparation, and analysis - Tan, Kim H. (Taylor & Francis, 2005)
As with the highly popular original, this new edition of Soil Sampling, Preparation, and Analysis provides students with an exceptionally clear description of the sampling and analysis methods most commonly used in modern soil laboratories around the world. What sets it apart as the first choice of professors is the grounding it offers in fundamental principles, professional protocols, and specific procedures. What makes it especially popular with students is that it spares them from having to tote large volumes for the sake of a page or two.